Dari Klik Ke Pasar: Peran Media Sosial Dalam Menembus Batas Produk Lokal - Indarsih, Fajar (Jurnal Manajemen dan Ilmu Administrasi, 2025)
This study aims to analyze the role of social media as an effective communication channel in increasing the reach and competitiveness of local products in a wider market. In the digital era, social media has developed into a platform that allows business actors, especially MSMEs, to utilize technological advantages in direct and efficient product marketing. Through a qualitative approach, this study explores how local business actors use social media to introduce their products, build brands, and interact with consumers. Data were collected through interviews with small business owners, observations of social media accounts used for marketing, and analysis of published content. The results of the study indicate that social media provides great opportunities for local business actors to expand their market, increase brand visibility, and build closer relationships with consumers. However, challenges such as limited digital literacy, unstructured content management, and difficulties in managing customer interactions professionally are still major obstacles. This study concludes that to maximize the potential of social media, local business actors need to improve their understanding of digital marketing strategies, more systematic content management, and be responsive to consumer needs.